Tonality: The Shape of Affect - Doantan-Dack, Mine (Empirical Musicology Review, 2013)
The last decade has witnessed an increasing interest in studying music as it relates to human evolution, leading to the establishment of so-called evolutionary musicology as a new field of enquiry. Researchers in this field maintain that music indeed played as crucial a role as the development of language in the evolution of humankind. The most frequently cited musical phenomena in relation to various adaptive functions include rhythm, meter, and melodic contour. In this connection, the universal phenomenon of tonal organisation of pitch in musical systems received no attention. This article provides a hypothesis regarding the evolutionary origins of tonality as a system for the dynamic shaping of affect, and establishes further connections between music and affective states by proposing a link between the emergence of tonality and of the human capacity to regulate inter-subjective dynamics by shaping the course of affect towards stable states. The article also proposes that tonality provides an archetypal psychological space within which the human ability to shape different paths towards stable affective states could evolve.